Flame-retardant polyurethane foaming filler and preparation process thereof
By using polyethalis glycol, polyether triexol, phosphorus, phosphate, phosphor nitrogen retardant response to isocyanate reactions, combined with the addition of modified basalt fiber, solving the flammable of polyurethane foam filler The problem achieves efficient flame retardant effects and environmental protection.
Patent Information
- Application Number
- CN202411456063.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-18
AI Technical Summary
Polyurethane rigid foam is a flammable material that burns fast and produces toxic smoke. How to develop a flammable self-extinguishing polyurethane foam filler to prevent the spread of fires and protect life and property safety.
The white material composition including polyether glycol, polyether triol, phosphorus flame retardant and phosphorus nitrogen flame retardant is reacted with isocyanate to form polyurethane foam with excellent performance, and in the foaming material Modified basalt fiber is added to improve the flame retardant effect.
The good flame retardant effect of polyurethane foam filler can form a solid carbonized layer and release non -gas gas during combustion, reduce oxygen content, improve flame retardant efficiency and environmental protection, and avoid the production of toxic by -products.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and more specifically, to a flame retardant polyurethane foaming filler and a preparation process thereof. Background Art
[0002] Polyurethane foam sealant is a single-component, moisture-curing, multi-purpose polyurethane foam filling elastic sealing material, also known as polyurethane foam glue (commonly known as polyurethane foaming agent), which is an indispensable auxiliary product in the door, window and curtain wall industry. Polyurethane foam sealant is a mixture of isocyanate-terminated prepolymers with catalysts, flame retardants, foaming agents, and plasticizers. It is a foaming material used in conjunction with physical foaming agents and gas propellants. After the prepolymer is sprayed out, it reacts chemically with water vapor in the air or moisture on the surface of the substrate, and then cross-links and solidifies. During construction, the aerosol colloid is sprayed to the construction site through a matching glue gun or manual spray tube, and the molding, foaming, bonding and sealing processes are completed in a short period of time. The construction operation is simple, and the on-site foaming is convenient for filling gaps of any shape, and it is tightly connected to the substrate on the bonding surface, especially the connection and sealing of doors and windows and walls. Its bonding strength exceeds the tear strength of the polyurethane foam itself. The solidified foam has multiple effects such as filling, bonding, sealing, heat insulation, waterproofing and noise absorption. As a building insulation material for doors, windows and curtain walls, polyurethane foam filler breaks the common problem of traditional building materials that waterproofing is not thermal insulation, thermal insulation is not waterproof, and once the waterproof layer leaks, the thermal insulation layer will immediately lose its thermal insulation function.
[0003] However, polyurethane rigid foam itself is a kind of flammable polymer material, and it burns very quickly, and will produce a large amount of toxic smoke. How to develop a flame-retardant and self-extinguishing product that can extinguish itself away from open flames and effectively prevent the spread of fire and protect the lives and property of residents has raised new difficulties. Summary of the invention
[0004] In order to make the polyurethane foam filler have a better flame retardant effect, the present application provides a flame retardant polyurethane foam filler and a preparation process thereof.
[0005] In a first aspect, the present application provides a flame retardant polyurethane foam filler, which adopts the following technical solution:
[0006] A flame retardant polyurethane foaming filler comprises the following raw materials in parts by weight: 300-400 parts of a white material composition, 220-250 parts of a black material, 60-70 parts of dimethyl ether, and 75-80 parts of propane-butane; the white material composition comprises the following raw materials in parts by weight: 95-105 parts of a polyether diol, 130-150 parts of a polyether triol, 30-45 parts of a foam leveling agent, 12-18 parts of a catalyst, 460-500 parts of a plasticizer, and 210-250 parts of a flame retardant; the flame retardant comprises a phosphorus flame retardant and a phosphorus-nitrogen flame retardant in a mass ratio of 1:0.5-0.6.
[0007] By adopting the above technical scheme, polyether diol and polyether triol are used as the main components of the white material composition, and react with black material isocyanate to form a polyurethane foam with excellent performance. The polyether polyol (including diol and triol) contains abundant hydroxyl groups, which can react quickly with the isocyanate group in isocyanate to form a stable polyurethane structure. By adjusting the amount of polyether diol and polyether triol, better fluidity can be obtained, which is helpful to obtain a uniform and delicate foam structure and can effectively control the physical properties of the polyurethane filler such as density, hardness and elasticity; phosphorus-based flame retardants and phosphorus-nitrogen-based flame retardants can form a medium containing NP bonds during the reaction. Intermediates, this structure can improve the carbonyl reaction activity and phosphorylation rate, and increase the carbonization rate. At the same time, nitrogen compounds can delay the volatilization loss of phosphorus compounds in the condensed phase, and enhance the oxidation of phosphorus compounds, releasing non-flammable gases such as ammonia and nitrogen, thereby improving the flame retardant efficiency. Phosphorus-based flame retardants mainly prevent combustion by forming a carbonized layer, while phosphorus-nitrogen-based flame retardants can release non-flammable gases during thermal decomposition and promote the formation of an expanded carbon layer. The combination of the two can form a more stable and efficient flame retardant system, and both flame retardants are environmentally friendly flame retardants with low toxicity and low smoke. They will not produce toxic and harmful by-products during combustion, reducing the harm to humans and the environment.
[0008] Optionally, the phosphorus-based flame retardant includes chlorinated alkane phosphate, flame retardant TCPP and triphenyl phosphate in a mass ratio of 1:0.7:0.3-0.5.
[0009] By adopting the above technical scheme, the chlorine and phosphorus elements in chlorinated alkane phosphate and TCPP can promote the formation of the carbon layer and increase its stability during the combustion process, while the phosphorus element can generate compounds such as phosphoric acid at high temperature, further promoting the formation of the carbon layer and effectively isolating oxygen and heat. At the same time, the addition of triphenyl phosphate can further improve the stability and density of the carbon layer, thereby enhancing the overall flame retardant effect. TCPP has good processability and stability, and is fully compatible with polymer materials. When used in combination with chlorinated alkane phosphate and triphenyl phosphate, it can maintain the physical properties of the material and the stability of the processing technology, and improve the flame retardant properties, processability and thermal stability of the polyurethane foaming filler.
[0010] Optionally, modified basalt fiber is further added to the flame retardant, and the mass ratio of the modified basalt fiber to the phosphorus-based flame retardant is 1:0.1-0.3. The preparation method of the modified basalt fiber is as follows:
[0011] Add polyvinyl alcohol and polyacrylamide to deionized water, stir to dissolve, add basalt fiber, ultrasonicate for 20-30 minutes, add boric acid, stir evenly, adjust the pH to 9-9.5 with sodium hydroxide solution, let stand, and dry to obtain modified basalt fiber. The mass ratio of basalt fiber, polyvinyl alcohol and polyacrylamide is 3-4:2.5-3:1.5-2.
[0012] By adopting the above technical scheme, the tensile strength of basalt fiber is higher than that of glass fiber, and it has excellent elastic modulus and stable chemical properties. It shows a very wide working temperature range and excellent high temperature resistance. At the same time, it has the advantages of excellent fire resistance, high temperature resistance, no melt dripping, no thermal shrinkage, etc. Polyvinyl alcohol is a water-soluble polymer material. There are extremely strong hydroxyl (-OH)O atoms in the molecular chain. It has strong adhesion, good mechanical properties and biocompatibility. Polyacrylamide is an organic linear polymer. There are a large number of carbonyl and amide groups on the molecular chain. It can form associative hydrogen bonds with surrounding molecules. It has active chemical properties, a typical three-dimensional network structure, good adhesion and thickening properties. Polyvinyl alcohol can form a cross-linked network structure under the action of boric acid, and the gel has good elasticity and high mechanical strength. There are a large number of hydroxyl, carbonyl and amide groups in the molecular chains of polyacrylamide and polyvinyl alcohol, which can interact with water molecules through intermolecular hydrogen bonds. At the same time, intermolecular hydrogen bonds can be formed between the two to achieve a secondary cross-linking effect, forming a double network gel structure on the surface of the basalt fiber.
[0013] Modified basalt fiber acts as a heterogeneous nucleating agent, which increases the bubble nucleation sites, has a positive effect on the formation of foam, and can increase the strength of the foaming component, avoid collapse due to insufficient strength in the foaming stage, and increase the dimensional stability of the foam; and the water molecules in the double network gel structure on the modified basalt fiber can produce an endothermic cooling effect. During the heating process, the movement of water molecules intensifies and evaporates rapidly, thereby absorbing heat and lowering the ambient temperature. In addition, the double network structure can release a part of the free water molecules in the early stage; after the temperature rises, the double network structure is destroyed, the hydrogen bonds are broken, and the water molecules are continuously released, increasing the cooling effect. In addition, the good thermal stability of basalt fiber hinders the movement of water molecules in the gel system, increases the residence time, and makes the water evaporation endothermic process continue, thereby improving the flame retardant and fire extinguishing effect.
[0014] After being dispersed, the modified basalt fiber is filled into the foaming material, playing a covering and filling role in the oxidation heating stage, so that the oxygen adsorption area of the polyurethane foam material is reduced, the oxygen absorption amount is reduced, and the flame retardant effect is played; when the temperature continues to rise, the double network gel structure is thermally decomposed to release basalt fiber. Basalt fiber has good thermal stability and is not easily decomposed by heat. When the double network gel structure is destroyed, it continues to fill the pores of the polyurethane foam to play a filling and plugging role. When the combustion continues to heat up, the basalt fiber structure decomposes and releases metal ions such as Al and Si to act on the polyurethane filler, so that the re-ignition reaction is hindered, and a dual inhibitory effect is played on preventing re-ignition.
[0015] Optionally, the basalt fiber is pretreated as follows:
[0016] Ultra-high molecular weight polyethylene, 2,5-bis(tert-butylperoxide-2,5-dimethyl-3-hexyne) and hydroxylated multi-walled carbon nanotubes are mixed and hot-melted to obtain a melt, 0.5-1 times the mass of basalt fiber as much as the mass of the melt is added, mixed, extruded and granulated, and the mass ratio of ultra-high molecular weight polyethylene, 2,5-bis(tert-butylperoxide-2,5-dimethyl-3-hexyne) and hydroxylated multi-walled carbon nanotubes is 1:0.01-0.15:0.04-0.08.
[0017] By adopting the above technical scheme, ultra-high molecular weight polyethylene has excellent flame retardancy. When subjected to a fire source, a carbonized layer can be quickly formed to isolate the contact between oxygen and the inside of the material, thereby effectively inhibiting the spread of flames. The carbonized layer has a good heat-insulating effect and can reduce heat transfer. The hydroxylation modification improves the dispersibility and compatibility of the ultra-high molecular weight polyethylene by introducing hydroxyl groups on the multi-walled carbon nanotubes, making their distribution more uniform, thereby exerting better reinforcement and flame retardant effects. The hydroxylated multi-walled carbon nanotubes have high thermal stability and high temperature resistance, can maintain structural stability in a high temperature environment, are not prone to thermal decomposition or melting, can effectively prevent the spread of fire, and have good thermal conductivity to quickly transfer heat from the fire source to the surrounding environment, thereby reducing the temperature of the fire source. By utilizing the adhesion effect of ultra-high molecular weight polyethylene, the hydroxylated multi-walled carbon nanotubes can assist the basalt fibers to form a stable carbon layer covering the surface of the material during combustion, thereby preventing the penetration of oxygen and combustible gases and inhibiting the combustion reaction.
[0018] Optionally, 20-40 parts of modified epoxy resin are also added to the white material composition. The preparation method of the modified epoxy resin is as follows: in parts by weight, 20-40 parts of epoxy resin, 0.1-0.2 parts of silicon coupling agent and 0.05-0.1 parts of dibutyltin dilaurate are mixed, stirred at 55-60°C under nitrogen protection, 50-100 parts of zinc oxide and 30-70 parts of POSS are added, and mixed evenly to obtain the modified epoxy resin.
[0019] By adopting the above technical scheme, amino groups are introduced into epoxy resin through silane coupling agent. Amino groups also serve as effective hydrogen bonding sites in the system, thereby increasing the degree of hydrogen bonding between epoxy resin and polyurethane. Moreover, the rigid aromatic rings in epoxy resin have higher regularity, thereby improving the regularity of molecular chains to a certain extent, improving the degree of microphase separation of materials, thereby improving the dimensional stability of polyurethane materials. Moreover, it contains ether bonds and hydroxyl groups, which are beneficial to improving wettability and adhesion, and has strong bonding ability to zinc oxide. Under the action of silane coupling agent, zinc oxide is evenly dispersed with epoxy resin, and there is a strong interface interaction. When the modified epoxy resin is added to the polyurethane raw material, the epoxy resin can regulate zinc oxide so that it can be evenly and densely distributed on the inner wall of the pores of the foaming material. As a heterogeneous nucleating agent, it can increase the pore density, thin the pore wall, and shrink. The shrinkage rate is reduced, the dimensional stability is increased, and the addition of zinc oxide can improve the flame retardancy of polyurethane foam. The heat released during the combustion process can be quickly transferred and consumed, reducing the combustion heat and increasing the limiting oxygen index. POSS is polymethyl silsesquioxane, which can enhance the stability of the carbon layer, so that the carbon layer formed by the combustion of epoxy resin is not easily destroyed by heat convection, and also prevents the contact between heat and oxygen, improves the flame retardant effect of the modified epoxy resin itself, and reduces the weakening of flame retardancy caused by the addition of epoxy resin. POSS is a polycarboxyl cage-type phenyl silsesquioxane. The surface polar groups of polycarboxyl cage-type phenyl silsesquioxane react chemically with the amino and hydroxyl groups in the epoxy resin, and have intermolecular forces with zinc oxide, thereby improving the bonding strength between the components in the modified epoxy resin, and then enhancing the interface force of the polyurethane foam filler on various types of filling materials.
[0020] Optionally, low molecular weight polyphenylene ether is further added in the preparation method of the modified epoxy resin, and the mass ratio of the low molecular weight polyphenylene ether to the epoxy resin is 1:0.15-0.2.
[0021] By adopting the above technical scheme, the polyphenylene ether has excellent mechanical properties, excellent dimensional stability, high strength, high hardness, strong rigidity, strong creep resistance and good heat resistance, and the low molecular weight polyphenylene ether has good compatibility with epoxy resin and is evenly dispersed in the modified epoxy resin. When the polyurethane is foamed, it acts as a heterogeneous nucleating agent to increase the nucleation sites and reduce the thickness of the pore wall, thereby providing favorable conditions for the preparation of an open-cell structure. The polyphenylene ether exists on the pore wall in the form of a dispersed phase, which is conducive to inducing stress and causing the pore wall to rupture during the foaming process, can increase the foaming ratio, and is conducive to forming an open-cell structure, thereby increasing the porosity of the polyurethane foaming filler and improving the pore uniformity.
[0022] Optionally, the plasticizer is one or more of environmentally friendly chlorinated paraffin, epoxidized soybean glyceride, aromatic oil and alkyl sulfonyl phenyl ester.
[0023] By adopting the above technical solution, the plasticizer can reduce the viscosity of the polyurethane foam material during the mixing process, making it easier to mix and process, and increase its flexibility and elongation. This makes the product softer and easier to bend, and improves its comfort and durability, which can extend the service life, simplify the production process, improve production efficiency, and reduce energy consumption, increase the plasticity of the mixed rubber, improve the processing performance and low-temperature performance of the vulcanized rubber, so that the product can still maintain good performance in a low-temperature environment.
[0024] Optionally, the foam leveling agent is one or more of modified silicone oil, polyacrylamide, polyvinyl alcohol, cellulose and sodium dodecyl sulfate.
[0025] By adopting the above technical solution, the foam leveler can increase the viscosity of the foam, reduce the fluidity of the foam, enhance the stability of the foam, prevent the foam from bursting prematurely, and give the foam good elasticity and self-repairing ability.
[0026] Optionally, the catalyst is bismorpholine diethyl ether;
[0027] The black material is polyisocyanate, which is selected from at least one of TDI, MDI and PAPI.
[0028] By adopting the above technical scheme, bismorpholine diethyl ether can accelerate the curing reaction of polyurethane, increase the reaction speed, shorten the curing time, improve the production efficiency, and also prolong the storage period of the polyurethane foaming filler.
[0029] MDI is diphenylmethane diisocyanate, which has high reactivity and functionality. TDI is toluene diisocyanate. PAPI has high functionality and viscosity. The polyurethane foam filler produced by this method has good foam density, and the gun can be discharged smoothly during construction without gun blockage.
[0030] In a second aspect, the present application provides a preparation process of a flame retardant polyurethane foam filler, which adopts the following technical solution:
[0031] A preparation process of a flame retardant polyurethane foam filler comprises the following steps:
[0032] The polyether diol, polyether triol, foam leveling agent, catalyst, flame retardant, modified epoxy resin, plasticizer and toughening agent are mixed uniformly to form a white material composition, with a stirring speed of 140-170 rpm and a stirring temperature of 30-40° C.;
[0033] After the white material mixture and the black material are alternately poured into the aerosol material tank, it is immediately sealed with a sealing machine, and dimethyl ether and propane and butane are added in sequence and shaken thoroughly. The reaction is carried out for 20-24 hours and then cooled to room temperature.
[0034] By adopting the above technical scheme, polyether diol, polyether triol, etc. are first mixed to form a white material composition, and then mixed with isocyanate and foaming agent, the molecular structure and properties of the white material composition can be more accurately controlled to ensure its reactivity and foam performance when mixed with black material. This step-by-step synthesis method helps to reduce the uncertainty in the reaction process and improve product quality. Moreover, this method is more flexible and adaptable to the market demand for the use of polyurethane foaming fillers. Moreover, since the white material composition and the black material have high reactivity when mixed, the foaming reaction can be triggered faster, and the production efficiency can be improved. At the same time, the occurrence of side reactions can also be reduced, the purity of the product can be improved, and the microstructure of the polyurethane foam filler, such as the size, distribution and density of the bubbles, can be better controlled, which helps to improve the mechanical properties of the product. Compared with the one-step method, manual foaming, etc., the process is easier to adjust, the product has better stability and consistency, and the production efficiency is high, which is suitable for large-scale production.
[0035] In summary, this application has the following beneficial effects:
[0036] 1. Since the present application adopts polyether diol and polyether triol as white material composition, and mixes with black material, propane and dimethyl ether for foaming, and uses a specific proportion of phosphorus flame retardant and phosphorus nitrogen flame retardant in the white material composition, a solid carbonized layer can be formed during combustion, and non-combustible gas is released, the oxygen content is reduced, the flame retardant efficiency and flame retardant effect are improved, and it is more environmentally friendly and does not release harmful gases.
[0037] 2. In the present application, it is preferred to add a certain amount of modified basalt fiber to the flame retardant, and to synthesize a double network structure on the basalt fiber to improve the flame retardant effect of the polyurethane foam filler. On the one hand, the water molecules in the double network structure are released to reduce the combustion temperature. On the other hand, after the double network structure is destroyed, the basalt fiber itself has strong heat resistance and fireproof effects, and can continue to play a flame retardant effect. In addition, the basalt fiber is pretreated with ultra-high molecular weight polyethylene, initiator and hydroxylated multi-walled carbon nanotubes to improve the flame retardant effect of the basalt fiber.
[0038] 3. In the present application, it is preferred to add modified epoxy resin to the white material composition. Through raw materials such as epoxy resin, silane coupling agent, zinc oxide and POSS, epoxy resin can improve and regulate the uniform and dense distribution of zinc oxide on the inner wall of the bubble cavity, so that the carbon layer formed by the combustion of the polyurethane foaming filler after combustion is relatively dense, and zinc oxide can consolidate the strength of the carbon layer and enhance the oxygen index, thereby further improving the flame retardant effect. DETAILED DESCRIPTION
[0039] The following examples further illustrate the present application in detail.
[0040] Preparation Example 1-7 of Modified Basalt Fiber
[0041] Preparation Example 1: Add 40g of polyvinyl alcohol and 30g of polyacrylamide to 1000g of deionized water, stir to dissolve, add 20g of basalt fiber, ultrasonicate at a frequency of 30kHz for 30min, add 1g of boric acid, stir evenly, adjust the pH to 9 with a 2wt% sodium hydroxide solution, let stand, and dry at 50°C for 4h to obtain modified basalt fiber. The mass ratio of basalt fiber, polyvinyl alcohol and polyacrylamide is 4:3:2, the polyvinyl alcohol brand is 2488, the molecular weight of polyacrylamide is 16 million, and the length of basalt fiber is 6mm.
[0042] Preparation Example 2: Add 30g of polyvinyl alcohol and 25g of polyacrylamide to 1000g of deionized water, stir to dissolve, add 15g of basalt fiber, ultrasonicate at a frequency of 30kHz for 30min, add 1g of boric acid, stir evenly, adjust the pH to 9.5 with a 2wt% sodium hydroxide solution, let stand, and dry at 50°C for 4h to obtain modified basalt fiber. The mass ratio of basalt fiber, polyvinyl alcohol and polyacrylamide is 3:2.5:1.5, the polyvinyl alcohol brand is 2488, the molecular weight of polyacrylamide is 16 million, and the length of basalt fiber is 6mm.
[0043] Preparation Example 3: Add 40g of polyvinyl alcohol to 1000g of deionized water, stir to dissolve, add 20g of basalt fiber, ultrasonicate at a frequency of 30kHz for 30min, add 1g of boric acid, stir evenly, adjust the pH to 9 with a 2wt% sodium hydroxide solution, let stand, and dry at 50°C for 4h to obtain modified basalt fiber. The mass ratio of basalt fiber to polyvinyl alcohol is 4:3, the polyvinyl alcohol brand is 2488, and the basalt fiber length is 6mm.
[0044] Preparation Example 4: The difference from Preparation Example 1 is that no boric acid is added.
[0045] Preparation Example 5: The difference from Preparation Example 1 is that the basalt fiber is pretreated as follows:
[0046] 100g of ultra-high molecular weight polyethylene, 2,5-bis(tert-butylperoxide-2,5-dimethyl-3-hexyne) and hydroxylated multi-walled carbon nanotubes were mixed, heated to 150°C for hot melting to obtain a melt, 1 times the total weight of basalt fiber was added to the melt, mixed, extruded and granulated, the mass ratio of ultra-high molecular weight polyethylene, 2,5-bis(tert-butylperoxide-2,5-dimethyl-3-hexyne) and hydroxylated multi-walled carbon nanotubes was 1:0.15:0.08, the ultra-high molecular weight polyethylene was selected from Mitsui L5000, and the hydroxylated multi-walled carbon nanotubes were selected from Sichuan Kenye Technology, model KYSCNT-C002.
[0047] Preparation Example 6: The difference from Preparation Example 1 is that the basalt fiber is pretreated as follows:
[0048] 100g of ultra-high molecular weight polyethylene solution, 2,5-bis(tert-butylperoxide-2,5-dimethyl-3-hexyne) and hydroxylated multi-walled carbon nanotubes were mixed, heated to 150°C for hot melting to obtain a melt, 1 times the total weight of basalt fiber of the melt was added, mixed, extruded and granulated, the mass ratio of ultra-high molecular weight polyethylene, 2,5-bis(tert-butylperoxide-2,5-dimethyl-3-hexyne) and hydroxylated multi-walled carbon nanotubes was 1:0.01:0.04, the ultra-high molecular weight polyethylene was selected from Mitsui L5000, and the hydroxylated multi-walled carbon nanotubes were selected from Sichuan Kenye Technology, model KYSCNT-C002.
[0049] Preparation Example 7: The difference from Preparation Example 6 is that no hydroxylated multi-walled carbon nanotubes are added.
[0050] Preparation Example 8-15 of Modified Epoxy Resin
[0051] Preparation Example 8: 40g of epoxy resin, 0.2g of silicon coupling agent KH550 and 0.1g of dibutyltin dilaurate are mixed, stirred at 55°C under nitrogen protection, 100g of zinc oxide, 70g of POSS and 8g of low molecular weight polyphenylene ether are added, and mixed evenly to obtain a modified epoxy resin. The epoxy resin is bisphenol A type epoxy resin E51, POSS is polycarboxyl cage-type phenyl silsesquioxane, selected from Hangzhou Tuomu Technology, model B-140, and the low molecular weight polyphenylene ether is selected from Sabic, model SA90.
[0052] Preparation Example 9: 20g of epoxy resin, 0.1g of silicon coupling agent KH550 and 0.05g of dibutyltin dilaurate are mixed, stirred at 60°C under nitrogen protection, 50g of zinc oxide, 30g of POSS and 3g of low molecular weight polyphenylene ether are added, and mixed evenly to obtain a modified epoxy resin. The epoxy resin is bisphenol A type epoxy resin E51, POSS is polycarboxyl cage-type phenyl silsesquioxane, selected from Hangzhou Tuomu Technology, model B-140, and the low molecular weight polyphenylene ether is selected from Sabic, model SA90.
[0053] Preparation Example 10: The difference from Preparation Example 8 is that zinc oxide, POSS and low molecular weight polyphenylene ether are not added.
[0054] Preparation Example 11: The difference from Preparation Example 8 is that no low molecular weight polyphenylene ether is added.
[0055] Preparation Example 12: The difference from Preparation Example 8 is that an equal amount of POSS is used to replace the low molecular weight polyphenylene ether.
[0056] Preparation Example 13: The difference from Preparation Example 8 is that an equal amount of zinc oxide is used to replace POSS.
[0057] Preparation Example 14: The difference from Preparation Example 8 is that an equal amount of low molecular weight polyphenylene ether is used instead of zinc oxide.
[0058] Preparation Example 15: The difference from Preparation Example 8 is that an equal amount of POSS is used to replace zinc oxide.
[0059] Example
[0060] Embodiment 1: A flame retardant polyurethane foam filler, comprising 350g of a white material composition, 230g of a black material, 65g of dimethyl ether and 78g of propane, wherein the black material is an isocyanate, specifically TDI (toluene diisocyanate) selected from Jinan Jinsheng New Materials, model TDI-80, and the white material composition is prepared by mixing the following raw materials by weight: 100g of polyether diol, 140g of polyether triol, 35g of a leveling agent, 15g of a catalyst, 480g of a plasticizer, and 230g of a flame retardant, wherein the polyether diol is selected from Guangzhou Yinghong Chemical, model N210, the polyether triol is selected from Jiangsu Xinsu New Materials, item number 303b, and the leveling agent It is modified silicone oil, selected from Jiashan Jiangnan Textile Materials, model JF-203, the catalyst is dimorpholine diethyl ether, the plasticizer is environmentally friendly chlorinated paraffin, selected from Xuzhou Pei Ze New Materials, item number 50#, the flame retardant includes 145g of phosphorus flame retardant and 85g of phosphorus-nitrogen flame retardant, the phosphorus flame retardant includes chlorinated alkane phosphate, flame retardant TCPP and triphenyl phosphate in a mass ratio of 1:0.7:0.5, phosphorus-nitrogen flame retardant TF-611, lattice momentum (Shanghai) new material, flame retardant TCPP is selected from Zhangjiagang Yarui Chemical, item number 103, and the chlorinated alkane phosphate is tris(1,3-dichloroisopropyl) phosphate (TDCPP).
[0061] The preparation process of the flame retardant polyurethane foam filler comprises the following steps:
[0062] The polyether diol, polyether triol, foam leveling agent, catalyst, flame retardant, modified epoxy resin, plasticizer and toughening agent are mixed uniformly to form a white material composition, with a stirring speed of 170 rpm and a stirring temperature of 30° C.;
[0063] 350g of the white material composition and 230g of the black material were alternately poured into the aerosol material can, and then the can was immediately sealed with a sealing machine. After sealing, 65g of dimethyl ether and 79g of propane and butane were added in sequence, shaken thoroughly, reacted for 24h, and cooled to room temperature.
[0064] Embodiment 2: A flame retardant polyurethane foaming filler, comprising 300g of a white material composition, 220g of a black material, 60g of dimethyl ether and 75g of propane, wherein the black material is an isocyanate, specifically diphenylmethane diisocyanate MDI, selected from Hebei Shengmao Chemical, model PM200, the white material composition is prepared by mixing the following raw materials by weight: 95g of polyether diol, 130g of polyether triol, 30g of a foam leveling agent, 12g of a catalyst, 460g of a plasticizer, and 210g of a flame retardant, the polyether diol is selected from Guangzhou Yinghong Chemical, model N210, the polyether triol is selected from Jiangsu Xinsu New Materials, model 303b, the foam leveling agent is modified Silicone oil, selected from Jiashan Jiangnan Textile Materials, model JF-203, the catalyst is dimorpholine diethyl ether, the plasticizer is environmentally friendly chlorinated paraffin, selected from Xuzhou Pei Ze New Materials, item number 50#, the flame retardant includes 140g of phosphorus flame retardant and 70g of phosphorus-nitrogen flame retardant, the phosphorus flame retardant includes chlorinated alkane phosphate, flame retardant TCPP and triphenyl phosphate in a mass ratio of 1:0.7:0.3, the flame retardant TCPP is selected from Zhangjiagang Yarui Chemical, item number 103, the chlorinated alkane phosphate is tris(1,3-dichloroisopropyl) phosphate (TDCPP), and the phosphorus-nitrogen flame retardant is selected from Lattice Momentum (Shanghai) New Materials, model TF-611.
[0065] The preparation process of the flame retardant polyurethane foam filler comprises the following steps:
[0066] The polyether diol, polyether triol, foam leveling agent, catalyst, flame retardant, modified epoxy resin, plasticizer and toughening agent are mixed uniformly to form a white material composition, with a stirring speed of 140 rpm and a stirring temperature of 40° C.;
[0067] 300g of the white material composition and 220g of the black material were alternately poured into the aerosol material can, and then the can was immediately sealed with a sealing machine. After sealing, 60g of dimethyl ether and 75g of propane and butane were added in sequence, shaken thoroughly, reacted for 20h, and cooled to room temperature.
[0068] Embodiment 3: A flame retardant polyurethane foaming filler, comprising 400g of a white material composition, 250g of a black material, 70g of dimethyl ether and 80g of propane, wherein the black material is an isocyanate, specifically PAPI (polyphenyl polymethylene polyisocyanate), having a molecular weight of 250.252 and a CSA number of 9016-87-9, selected from Zhejiang Hualang Products, the white material composition is prepared by mixing the following raw materials by weight: 105g of polyether diol, 150g of polyether triol, 45g of a foam leveling agent, 18g of a catalyst, 500g of a plasticizer, and 250g of a flame retardant, the polyether diol is selected from Guangzhou Yinghong Chemical, model N210, the polyether triol is selected from Jiangsu Xinsu New Materials, item number The composition is 303b, the foaming agent is modified silicone oil, selected from Jiashan Jiangnan Textile Materials, model JF-203, the catalyst is dimorpholine diethyl ether, the plasticizer is environmentally friendly chlorinated paraffin, selected from Xuzhou Pei Ze New Materials, model 50#, the flame retardant includes 156g of phosphorus flame retardant and 94g of phosphorus nitrogen flame retardant, the phosphorus flame retardant includes chlorinated alkane phosphate, flame retardant TCPP and triphenyl phosphate in a mass ratio of 1:0.7:0.4, the flame retardant TCPP is selected from Zhangjiagang Yarui Chemical, model 103, the chlorinated alkane phosphate is tris(1,3-dichloroisopropyl) phosphate (TDCPP), and the phosphorus nitrogen flame retardant is selected from Lattice Momentum (Shanghai) New Materials, model TF-611.
[0069] The preparation process of the flame retardant polyurethane foam filler comprises the following steps:
[0070] The polyether diol, polyether triol, foam leveling agent, catalyst, flame retardant, modified epoxy resin, plasticizer and toughening agent are mixed uniformly to form a white material composition, with a stirring speed of 140 rpm and a stirring temperature of 40° C.;
[0071] After 400g of the white material composition and 250g of the black material are alternately poured into the aerosol material can, the can is immediately sealed with a sealing machine. After sealing, 70g of dimethyl ether and 80g of propane and butane are added in sequence and shaken thoroughly. The mixture is reacted for 20h and cooled to room temperature.
[0072] Example 4: A flame-retardant polyurethane foam filler, which is different from Example 1 in that modified basalt fiber is also added to the flame retardant, the flame retardant includes a phosphorus-based flame retardant, a phosphorus-nitrogen-based flame retardant and modified basalt fiber in a mass ratio of 1:0.58:0.3, the modified basalt fiber is made from Preparation Example 1, the phosphorus-based flame retardant includes chlorinated alkane phosphate, flame retardant TCPP and triphenyl phosphate in a mass ratio of 1:0.7:0.4, the flame retardant TCPP is selected from Zhangjiagang Yarui Chemical, item number 103, the chlorinated alkane phosphate is tri(1,3-dichloroisopropyl) phosphate (TDCPP), and the phosphorus-nitrogen-based flame retardant is selected from Lattice Momentum (Shanghai) New Materials, model TF-611.
[0073] Example 5: A flame-retardant polyurethane foam filler, which is different from Example 1 in that modified basalt fiber is also added to the flame retardant, the flame retardant includes a phosphorus-based flame retardant, a phosphorus-nitrogen-based flame retardant and modified basalt fiber in a mass ratio of 1:0.58:0.1, the modified basalt fiber is made from Preparation Example 2, the phosphorus-based flame retardant includes chlorinated alkane phosphate, flame retardant TCPP and triphenyl phosphate in a mass ratio of 1:0.7:0.4, the flame retardant TCPP is selected from Zhangjiagang Yarui Chemical, item number 103, the chlorinated alkane phosphate is tri(1,3-dichloroisopropyl) phosphate (TDCPP), and the phosphorus-nitrogen-based flame retardant is selected from Lattice Momentum (Shanghai) New Materials, model TF-611.
[0074] Example 6: A flame retardant polyurethane foam filler, which is different from Example 4 in that the modified basalt fiber is made from Preparation Example 3.
[0075] Example 7: A flame retardant polyurethane foam filler, which is different from Example 4 in that the modified basalt fiber is made from Preparation Example 4.
[0076] Example 8: A flame retardant polyurethane foam filler, which is different from Example 4 in that the modified basalt fiber is made from Preparation Example 5.
[0077] Example 9: A flame retardant polyurethane foam filler, which is different from Example 4 in that the modified basalt fiber is made from Preparation Example 6.
[0078] Example 10: A flame retardant polyurethane foam filler, which is different from Example 4 in that the modified basalt fiber is made from Preparation Example 7.
[0079] Example 11: A flame retardant polyurethane foam filler, which is different from Example 4 in that an equal amount of basalt fiber is used to replace the modified basalt fiber.
[0080] Example 12: A flame-retardant polyurethane foam filler. The difference from Example 4 is that 40 g of modified epoxy resin is also added to the white material composition, and the modified epoxy resin is prepared by Preparation Example 8.
[0081] Example 13: A flame retardant polyurethane foam filler. The difference from Example 4 is that 20 g of modified epoxy resin is also added to the white material composition, and the modified epoxy resin is prepared by Preparation Example 9.
[0082] Example 14: A flame retardant polyurethane foam filler, which is different from Example 12 in that the modified epoxy resin is made from Preparation Example 10.
[0083] Example 15: A flame retardant polyurethane foam filler, which is different from Example 12 in that the modified epoxy resin is made from Preparation Example 11.
[0084] Example 16: A flame retardant polyurethane foam filler, which is different from Example 12 in that the modified epoxy resin is made from Preparation Example 12.
[0085] Example 17: A flame retardant polyurethane foam filler, which is different from Example 12 in that the modified epoxy resin is made from Preparation Example 13.
[0086] Example 18: A flame retardant polyurethane foam filler, which is different from Example 12 in that the modified epoxy resin is made from Preparation Example 14.
[0087] Example 19: A flame retardant polyurethane foam filler, which is different from Example 12 in that the modified epoxy resin is made from Preparation Example 15.
[0088] Example 20: A flame-retardant polyurethane foam filler. The difference from Example 8 is that 40 g of modified epoxy resin is also added to the white material composition, and the modified epoxy resin is prepared by Preparation Example 8.
[0089] Comparative Example
[0090] Comparative Example 1: A flame-retardant polyurethane foam filler, which is different from Example 1 in that the flame retardants are all phosphorus-nitrogen flame retardants.
[0091] Comparative Example 2: A flame-retardant polyurethane foam filler, which differs from Example 1 in that the flame retardants are all phosphorus-based flame retardants.
[0092] Comparative Example 3: A flame-retardant polyurethane foaming filler, which is different from Example 1 in that the phosphorus-based flame retardant is triphenyl phosphate.
[0093] Performance testing
[0094] The polyurethane foam filler was prepared according to the methods in the examples and comparative examples, and the performance was tested according to the following method. The test results are recorded in Table 1.
[0095] 1. Density: Test in accordance with GB / T6343-2009 "Determination of apparent density of foam plastics and rubber".
[0096] 2. Dimensional stability (23±2℃, 48h): The test shall be carried out in accordance with GB / T8811-2008 “Test method for dimensional stability of rigid foam plastics”.
[0097] 3. Bond strength: According to ASTM D3931-2008 "Standard test method for bond strength of crack-filling adhesives in shear tests by pressure load method"
[0098] 4. Limiting oxygen index: Tested in accordance with GB / T2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test".
[0099] Table 1 Performance test of polyurethane foam filler
[0100]
[0101]
[0102] It can be seen from the data in Table 1 that the flame retardant grade of the polyurethane foam filler prepared in Examples 1-3 reaches B2, and has a high bonding strength to aluminum plates, PVC plastic plates and cement mortar plates, which is convenient for filling gaps in different materials to obtain a long-term filling effect, and has high dimensional stability and is not prone to shrinkage.
[0103] In Example 4 and Example 5, the modified basalt fibers prepared in Preparation Example 1 and Preparation Example 2 are used in the flame retardant respectively. It can be seen from the data in Table 1 that the polyurethane foam sealants prepared in Example 4 and Example 5 have better dimensional stability, smaller shrinkage, stronger bonding ability to plates of various materials, and better flame retardancy.
[0104] In Example 6, the modified basalt fiber prepared in Preparation Example 3 was used, and compared with Example 4, polyacrylamide was not added. In Example 7, the modified basalt fiber prepared in Preparation Example 4 was used, and boric acid was not added. Table 1 shows that the oxygen index of the polyurethane foam filler prepared in Example 6 and Example 7 is reduced, the flame retardant effect is reduced, and the bonding strength is slightly weakened, and the dimensional stability is slightly reduced.
[0105] In Example 8 and Example 9, the modified basalt fibers prepared in Preparation Example 5 and Preparation Example 6 are used. Compared with Example 4, the polyurethane foam fillers prepared in Example 8 and Example 9 have increased dimensional stability and improved flame retardancy.
[0106] In Example 10, the modified basalt fiber prepared in Preparation Example 7 was used. Compared with Example 9, no hydroxylated multi-walled carbon nanotubes were added. It can be seen that the dimensional stability of the polyurethane foam filler was slightly reduced, and the oxygen index was reduced.
[0107] In Example 11, only basalt fiber is used in the flame retardant without modification. Compared with Example 4, it can be seen that all properties are reduced, but the bonding strength is slightly reduced compared with Example 1, indicating that adding unmodified basalt fiber can improve flame retardancy, but has an adverse effect on other properties of the polyurethane foam filler.
[0108] Compared with Example 4, Example 12 and Example 13 further added modified epoxy resins prepared by Preparation Example 8 and Preparation Example 9, respectively. The data in Table 1 show that the oxygen index of the polyurethane foam filler prepared in Example 12 and Example 13 is increased, the flame retardant effect is further improved, and the bonding strength with materials such as aluminum plates is greater, it is not easy to detach, the service life is longer, and the dimensional shrinkage is smaller and the dimensional stability is better.
[0109] In Example 14, the modified epoxy resin prepared in Preparation Example 10 was used. Compared with Example 12, zinc oxide, POSS and low molecular weight polyphenylene ether were not added. Table 1 shows that the flame retardant effect of the polyurethane foam filler is reduced, the bonding strength to materials such as PVC is weakened, and the dimensional stability is reduced.
[0110] In Example 15, the modified epoxy resin prepared in Preparation Example 11 was used. Compared with Example 12, no low molecular weight polyphenylene ether was added, the density of the polyurethane foaming filler was reduced, the foaming ratio was slightly reduced, and the other properties did not change much.
[0111] Example 16 Compared with Example 12, the modified epoxy resin prepared in Preparation Example 12 is used, wherein POSS is used instead of low molecular weight polyphenylene ether. As can be seen in Table 1, the flame retardant effect of the polyurethane foam filler is increased, the adhesion is enhanced, but the density is reduced.
[0112] Compared with Example 12, the modified epoxy resin in Example 17 uses zinc oxide instead of POSS, the oxygen index of the polyurethane foam filler is increased, the flame retardant effect is improved, the dimensional stability is increased, but the bonding effect is reduced.
[0113] In Example 18, the modified epoxy resin prepared in Preparation Example 14 is used. Compared with Example 12, low molecular weight polyphenylene ether is used instead of zinc oxide. The flame retardancy of the polyurethane foam filler prepared in Example 18 decreases, and the foaming performance increases.
[0114] In Example 19, the modified epoxy resin prepared in Preparation Example 15 is used. Compared with Example 12, POSS is used instead of zinc oxide. It can be seen from the data in Table 1 that the flame retardant effect of the polyurethane foam filler prepared in Example 19 is reduced, and the bonding effect is weakened.
[0115] Compared with Example 1, only phosphorus-nitrogen flame retardants are used in Comparative Example 1, and only phosphorus-based flame retardants are used in Comparative Example 2. Table 1 shows that the oxygen index of the polyurethane foam filler prepared in Comparative Example 1 and Comparative Example 2 is reduced, the flame retardant effect is reduced, and the foaming effect is worse, and the density is reduced; Compared with Example 1, Comparative Example 3 uses only triphenyl phosphate in the phosphorus-based flame retardant. It can be seen that the oxygen index of the polyurethane foam filler is reduced, and various performances are not as good as those in Example 1.
[0116] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A flame retardant polyurethane foam filler, characterized in that: The invention comprises the following raw materials in parts by weight: 300-400 parts of a white material composition, 220-250 parts of a black material, 60-70 parts of dimethyl ether, and 75-80 parts of propane-butane. The white material composition comprises the following raw materials in parts by weight: 95-105 parts of a polyether diol, 130-150 parts of a polyether triol, 30-45 parts of a foam leveling agent, 12-18 parts of a catalyst, 460-500 parts of a plasticizer, and 210-250 parts of a flame retardant. The flame retardant comprises a phosphorus-based flame retardant and a phosphorus-nitrogen-based flame retardant in a mass ratio of 1:0.5-0.
6.
2. The flame retardant polyurethane foam filler according to claim 1, characterized in that: The phosphorus-based flame retardant comprises chlorinated alkane phosphate, flame retardant TCPP and triphenyl phosphate in a mass ratio of 1:0.7:0.3-0.
5.
3. The flame retardant polyurethane foam filler according to claim 1, characterized in that: Modified basalt fiber is also added to the flame retardant, and the mass ratio of the modified basalt fiber to the phosphorus flame retardant is 1:0.1-0.
3. The preparation method of the modified basalt fiber is as follows: Add polyvinyl alcohol and polyacrylamide to deionized water, stir to dissolve, add basalt fiber, ultrasonicate for 20-30 minutes, add boric acid, stir evenly, adjust the pH to 9-9.5 with sodium hydroxide solution, let stand, and dry to obtain modified basalt fiber. The mass ratio of basalt fiber, polyvinyl alcohol and polyacrylamide is 3-4:2.5-3:1.5-2.
4. The flame retardant polyurethane foam filler according to claim 3, characterized in that: The basalt fiber is pretreated as follows: Ultra-high molecular weight polyethylene, 2,5-bis(tert-butylperoxide-2,5-dimethyl-3-hexyne) and hydroxylated multi-walled carbon nanotubes are mixed and hot-melted to obtain a melt, 0.5-1 times the mass of basalt fiber as much as the mass of the melt is added, mixed, extruded and granulated, and the mass ratio of ultra-high molecular weight polyethylene, 2,5-bis(tert-butylperoxide-2,5-dimethyl-3-hexyne) and hydroxylated multi-walled carbon nanotubes is 1:0.01-0.15:0.04-0.
08.
5. The flame retardant polyurethane foam filler according to claim 1, characterized in that: The white material composition is also added with 20-40 parts of modified epoxy resin. The preparation method of the modified epoxy resin is as follows: 20-40 parts of epoxy resin, 0.1-0.2 parts of silicon coupling agent and 0.05-0.1 parts of dibutyltin dilaurate are mixed by weight, stirred at 55-60° C. under nitrogen protection, 50-100 parts of zinc oxide and 30-70 parts of POSS are added, and mixed evenly to obtain the modified epoxy resin.
6. The flame retardant polyurethane foam filler according to claim 5, characterized in that: Low molecular weight polyphenylene ether is also added into the preparation method of the modified epoxy resin, and the mass ratio of the low molecular weight polyphenylene ether to the epoxy resin is 1:0.15-0.
2.
7. The flame retardant polyurethane foam filler according to claim 1, characterized in that: The plasticizer is one or more of environmentally friendly chlorinated paraffin, epoxy soybean glyceride, aromatic oil and alkyl sulfonyl phenyl ester.
8. The flame retardant polyurethane foam filler according to claim 1, characterized in that: The foam leveling agent is one or more of modified silicone oil, polyacrylamide, polyvinyl alcohol, cellulose and sodium lauryl sulfate.
9. The flame retardant polyurethane foam filler according to claim 1, characterized in that: The catalyst is bismorpholine diethyl ether; The black material is polyisocyanate, which is selected from at least one of TDI, MDI and PAPI.
10. The preparation process of the flame retardant polyurethane foaming filler according to any one of claims 1 to 9, characterized in that: The following steps are involved: The polyether diol, polyether triol, foam leveler, catalyst, flame retardant and plasticizer are mixed uniformly to form a white material composition, with a stirring speed of 140-170 rpm and a stirring temperature of 30-40°C; After the white material mixture and the black material are alternately poured into the aerosol material tank, it is immediately sealed with a sealing machine, and dimethyl ether and propane and butane are added in sequence and shaken thoroughly. The reaction is carried out for 20-24 hours and then cooled to room temperature.
Citation Information
Patent Citations
High-strength solvent-free polyurethane adhesive and preparation method thereof
CN104017532A
High-porosity foamed ceramic insulation board and preparation method thereof
CN111099906A
Wood composite articles
CN112292243A
B2-grade flame-retardant polyurethane foam joint mixture and preparation method thereof
CN114410269A
Preparation method and application of high-strength waterproof concrete for house construction
CN115159910A
Cited By
High-flame-retardant and high-wear-resistant winding cable
CN120690498A